PROSPECTS FOR A TRULY PORTABLE ABSOLUTE GRAVIMETER - Faller J.E.; Vitouchkine A.L. (My University, 2003)
We are in the process of developing a small portable absolute gravimeter that employs a cam-based dropping mechanism. The resulting high data rate (100 drops in 30 s) serves to compensate for the short (2 cm) dropping distance. We hope to achieve a measurement accuracy with this instrument of +/-5 μgal.